ACEH EAST COAST COMMUNITY ECONOMIC DEVELOPMENT (HISTORICAL STUDY AND EXISTENCE OF KUALA LANGSA PORT AND ITS CONTRIBUTION TO THE GOVERNMENT OF 1900-2018) - Usman Usman; Bachtiar Akob; Tengku Muhammad Sahudra (Universitas Negeri Medan, 2023)
The Port of Kuala Langsa in 1920 had a great opportunity for economic development during the Social Pacificization period, in addition to the interests of the Netherlands and the people of the east coast. trade routes: Asia and Europe. This port is supported by land transportation. Atjeh Tram Langsa supplies goods from the north coast straight to the port of Kuala. Atjeh Tram Tamiang took part in supplying rubber and palm oil commodities to the port of Kuala during the Dutch era for export-import trade abroad. Between 1916 and 1930, the export of traditional crops such as betel nut, 942,591 tons of pepper, and 8,300 tons of rice were to Penang. Modern (1925–1935) rubber plants (183,550 tons) and palm (9,819,047 tons) were exported to Europe. During the Japanese occupation (1942–1945), Kuala Port's exports and imports decreased drastically. After Indonesia's independence, in 1987, the port of Kuala resumed operations in the non-oil and gas sector, with exports of Ply wood of 4,216,402 tons and grumb rubber of 1,839,600 tons from PT. Gruti Bayeun Aceh Timur. Charcoal wood exports 5,534,000 tons to Hong Kong, Japan, Singapore, and Taiwan from Bayeun, Sei Pauh, and Sei Yu. Import types of goods: Phenol (7159 tons) and methanol (7159 tons). Between 1987 and 2002, at the port of Kuala, other goods were imported: cars, motorcycles, and drugs. In 2003–2007, they were again imported from Singapore and Malaysia: 9,206 tons of methanol, 6,384 tons of minerals, and 9,396 tons of basic necessities. In 2008–2018, Kuala Port still existed as a trade center in the economic sector of the Langsa City government with Asia based on the interests and economic growth of the community. The aims of this study were (1) to examine the pioneering of Kuala Langsa port as a maritime port on the east coast of Aceh; (2) the educational passification policy and Kuala Langsa port; (3) to find out the study of Kuala Langsa port facilities and infrastructure and its development in the east coast area; (4) to examine the role of the Kuala Langsa port in the export-import trade sector; and (5) to examine the impact of the Kuala Langsa port as the center of the government's economic area based on the people's economic interests. This study uses a critical historical method, the substance of which excludes inauthentic material and concludes that testimony that can be trusted from original material The critical historical method consists of four steps in the research process: collecting sources (heuristics); primary, secondary, and tertiary; criticizing sources, both internal and external; interpreting facts obtained from these sources; historiography; reconstructing existing facts and interpreting them in the form of historical writings; and critically synthesizing facts. The results of research on the Kuala Langsa port since the days of the Dutch, Japanese, and Indonesian governments were made as an international and transit port until it received international status in 2019. The conclusion is that the Kuala Langsa port has succeeded in contributing to the community and the government in the export sector of community and private government-owned plantation products.